DEMOKRASI CIVIL SOCIETY DI INDONESIA DAN INDIA: SEBUAH PERBANDINGAN - Gameal Flamirion; Muradi . (JWP (Jurnal Wacana Politik), 2016)
Indonesia and India are two countries with similarities in geographic, demographic and historical. The democratization process accelerates the development of civil societies sector in these countries. Democratization phenomena and development of civil society in both countries are an interesting object to be studied in the perspective of comparative politics. This paper aims to accurately describe democratization process and the development of civil society in both countries so that it can be compared at the level of theory and reality.